The convolution of facts and norms: new approach to legal reasoning and interpretation - Lamentowicz, Wojciech (Studia Iuridica Toruniensia, 2020)
My purpose is to show that facts and norms in real life are intermingled and cannot exist without symbiotic convolutions with each other. Keeping facts and norms as close as possible in the minds of interpreters is a pragmatic advise that can contribute to a better understanding of legal problems. Facts and norms in the process of law application exert a great deal of influence on each other. This dynamics of hidden, unspoken discourse between facts and norms creates meanings that all experts in law should be able to understand. Many legal professionals have quite limited capability of understanding the meaning of facts. It is related to the some fallacies of legal education. There is not enough attention paid to psychology and sociology in education of young lawyers. Lawyers should be better prepared to understand the culture of human beings and not just studying the art of playing with words in the statutory law enacted by parliaments.